2012
DOI: 10.1021/cg3013415
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses and Structures of Mononuclear, Dinuclear and Polynuclear Silver(I) Complexes of 2-Pyrazole-Substituted 1,10-Phenanthroline Ligands

Abstract: A series of mononuclear, dinuclear and polynuclear silver(I) complexes (1−6) bearing 2-pyrazolesubstituted 1,10-phenanthroline derivatives (L 1 , F L 1 , L 2 ) have been synthesized and characterized by 1 H and 13 C NMR, IR spectroscopy, elemental analysis, and single crystal X-ray diffraction. Reaction ofAg separation: 3.059(1) Å), as well as a dinuclear complex [Ag 2 (ClO 4 ) 2 (L 1 ) 2 ] (4) in which the perchlorate anions instead of solvents are involved in the metal coordination, have also been obtained. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…The emission also quenched which could be attributed to the heavy atom effect of Ag + (Figure f). The binding constant (K S ) was determined as 7.87×10 6 M −1 (Figure S6c,d) . 1 H NMR gave weaken and broaden signal (Figure S2).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The emission also quenched which could be attributed to the heavy atom effect of Ag + (Figure f). The binding constant (K S ) was determined as 7.87×10 6 M −1 (Figure S6c,d) . 1 H NMR gave weaken and broaden signal (Figure S2).…”
Section: Methodsmentioning
confidence: 99%
“…The binding constant (K S ) was determined as 7.87 × 10 6 M À 1 (Figure S6c,d). [10] 1 H NMR gave weaken and broaden signal (Figure S2). All these data indicated that DPC bound with Ag + in the phenanthroline motif.…”
Section: Tunable Supramolecular Nanoarchitectures Constructed By the mentioning
confidence: 99%
“…268 nm assignable to π-π* transition of aromatic rings of phenanthrolinebased ligands [35][36] . The remaining bands in the UV-vis region (320-330 nm) are attributed to intraligand transitions of the Schiff base.…”
Section: Synthesis Of Ligands and V-complexesmentioning
confidence: 99%
“…In addition, pyrazole-pyridine hybrid molecules were used as ligands for transition metal cations, and some of the obtained complexes were reported to exhibit promising luminescent properties, [10,11] as well as catalytic activity. For instance, some pyrazole-bipyridine metal chelates were reported as promising catalysts for the epoxidation reactions (in case of Ru-complexes [12] ), or catalysts for 1,3-butadiene polymerization reaction (in case of Co-complexes [13] ).…”
Section: Introductionmentioning
confidence: 99%